Pengaruh Digital Leadership, Work Engagement, dan Organization Experience terhadap Innovation Work Behavior pada Pekerja Generasi Z Berpengalaman Organisasi di Jawa Tengah - Sabrina Nabilla Afif; Agustina Fitrianingrum (ARZUSIN, 2025)
The rapid development of digital technology requires organizations to continually innovate in order to survive and remain competitive, making innovative work behavior (Innovation Work Behavior) a crucial factor, particularly among Generation Z workers who are actively engaged in organizational activities. However, previous studies have reported inconsistent findings regarding the factors that influence innovative work behavior, especially digital leadership, work engagement, and organizational experience. This study aimed to analyse the effects of digital leadership, work engagement, and organizational experience on Innovation Work Behavior among experienced workers who are actively involved in organizations in Central Java. A quantitative approach with an explanatory research design was employed, using purposive sampling of 271 respondents. Data were collected through an online questionnaire and analysed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that digital leadership, work engagement, and organizational experience have positive and significant effects on Innovation Work Behavior. These findings affirm that effective digital leadership, high levels of work engagement, and strong organizational experience can foster innovative work behavior among employees. The implications of this study recommend that organizations strengthen digital leadership capacities, enhance employee engagement, and leverage organizational experience as a strategic asset for innovation development and corporate sustainability.